The effect of implant modification: the low contact stress experience. (October 2019) - Pineda, Alfredo; Pabbruwe, Moreica B.; Kop, Alan M.; Vlaskovsky, Philip; Hurworth, Mark
Abstract : Aims: The aim of this study was to conduct the largest low contact stress (LCS) retrieval study to elucidate the failure mechanisms of the Porocoat and Duofix femoral component. The latter design was voluntarily recalled by the manufacturer. Materials and Methods: Uncemented LCS explants were divided into three groups: Duofix, Porocoat, and mixed. Demographics, polyethylene wear, tissue ingrowth, and metallurgical analyses were performed. Results: In 104 implants, a decrease in the odds of loosening and an increase in metallosis and tissue staining in the Duofix group relative to Porocoat group was detected (p = 0.028). There was an increased presence of embedded metallic debris in the Duofix group (p < 0.001). Decreased tissue ingrowth was associated with the Duofix surface (p < 0.001). The attached beads had reduced microhardness, indicative of adverse thermal processing, which resulted in bead shedding, particulate debris, and metallosis. Conclusion: Hydroxyapatite coating of the LCS femoral component produced unexpected results and led to its recall. The root cause was likely a combination of retained alumina grit and a reduction in bead microhardness (mechanical strength) resulting in increased particle debris, metallosis, and early revision. The Duofix LCS femoral component was not equivalent to the Porocoat version despite its approval through the Food and Drug Administration (FDA) 510(k) equivalance approval process. Regulation of the introduction of modified existing devices needs to be improved and the Duofix LCS should have been considered to be a new device for which equivalence had not been demonstrated at the point of introduction. Cite this article: Bone Joint J 2019;101-B:1248–1255